SISTEM PEWARISAN RITUAL KAAGO-AGO LIWU PADA MASYARAKAT KORONI DI KECAMATAN WAKORUMBA UTARA - La Ode Sahidin (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2016)
The study aims to find the model of inheritance of the ritual of kaago-ago liwu that existed in the Koroni sub-district of North Wakorumba. The method used to perform the analysis is the transmission method of Vansina. The results of this study indicate that there are four methods of inheritance used in ritual kaago-ago liwu that is (1) esoterik method, ritual kaago-ago liwu done in closed. This means that ritual katingka form can only be inherited through his offspring (blood relation); (2) mnemonic method in ritual kaago-ago liwu in form of disastrous diseases that hit the village. (3) The instruction method is used only by sara hukumu to transmit kaago-ago liwu in form of zikir. (4) The controlling method is a model of transmission in the ritual of kaago-ago liwu to evaluate the appropriateness of a person who leading the ritual. Keywords: ritual, kaago-ago liwu, Koroni society, North Buton